Educators in the Minang Region From an Islamic Perspective (Exploring the Role of Niniak Mamak) - Lindra, Afni; Iswantir, Iswantir; Indria, Anita; Khamim, Siti; Saparina, Kaila (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2026)
Mamak is also known as penghulu or Datuk in the Minangkabau community's governmental structure. Datuk has duties and responsibilities towards the education of Kemanakan. As society has developed rapidly, the Minangkabau region is no longer inhabited only by the Minang tribe, but also by people from outside the Minang tribe. Naturally, the duties of the Datuk as the highest leader in the traditional government structure in Minangkabau to educate the Kemanakan have increased. Moreover, in Minangkabau society, there are the terms Kandung Kemanakan and Malakok Kemanakan (children of adopted siblings). However, nowadays, sometimes the person entrusted as Datuk is not in Ranah Minang, some have migrated to other areas, leaving behind the duties that should be carried out in the village. Even those appointed as Datuk themselves were not born, raised and grew up in Ranah Minang but in other areas. As a tribe with the philosophy of adaik basandi syara', syara' basandi kitabullah (customs based on Sharia law, Sharia law based on the Holy Book), the implementation of these duties must be in accordance with Islamic teachings, where the Qur'an is the guideline for life. Observing this condition, it is necessary to conduct a study on the duties and responsibilities of the Datuk in educating kemanakan from an Islamic perspective. The purpose of this study is to determine the role of Mamak in educating kamanakan from the perspective of Islamic teachings, with the hope of revitalising the role of Mamak as educators in Minangkabau. The results of this study show that Mamak, as educators, have a responsibility to educate kamanakan in morals and provide education in social life, in accordance with Islamic teachings. This research is a literature study with a descriptive qualitative approach. The data collection techniques used were interviews and documentation studies.